Role stress and work engagement as antecedents of job satisfaction in Spanish workers - Alejandro Orgambídez-Ramos; Yolanda Borrego-Alés; Isabel Mendoza-Sierra (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: According to the Job Demands-Resources (JDR) model, engagement and job satisfaction may be produce by two types of working conditions: job demands (i.e. role stress) and job resources (i.e. self-efficacy). This study examines the role of role stress and work engagement as antecedents of job satisfaction in a sample of Spanish workers. Design/methodology/approach: This study comprised a sample of 435 Spanish workers. A cross sectional study was used to examine the relationship between role stress, work engagement and job satisfaction. Data were gathered based on personal administered questionnaires. Findings and Originality/value: Hierarchical multiple regression models have revealed that job satisfaction was significantly predicted by role stress and work engagement. Results support JDR model by showing that positive outcomes, such as job satisfaction can be predicted by motivational process and job demands. Research limitations/implications: The cross-sectional design cannot evidence of causal relationships. This study relies on self-reports, which might increase the risk of common method variance. Practical implications: On a practical level, the JDR model provides a framework for understanding motivating workplaces and engaged and satisfied employees. Originality/value: The JDR model could be useful in designing strategies for which engaged employees may be advantageous to improving the quality of services, while at the same time increasing employees' job satisfaction and well-being.
Keywords: 650; work engagement; role conflict; role ambiguity; job satisfaction; JDR model